Pengembangan Alat Pengukuran Kelelahan Mental Berbasis Uji Flicker - Yassierli Yassierli; Atya Nur Aisha; Azi Ginanjar Nugraha (Institute of Research and Community Outreach - Petra Christian University, 2016)
Previous studies have been conducted to measure fatigue using flicker test. However, the validity of the device is still unknown empirically. This study proposed a modification of fatigue measuring apparatus based on flicker test. The modifications were developed from the framework of human factors product design, with the stages including analysis of the existing condition, operational concept, user requirements, performance criteria, system requirements, design prototyping, usability testing and final testing. The proposed apparatus consists of two main parts: a stimulus source and a control device as input. The stimulus is given by three lights with adjustable position and orientation angle. A LCD screen was provided to display status and result of the measurement. The control device consists of three buttons to respond the stimulus accordingly. Product testings were done through 1) a laboratory experiment with activities of critical reading and arithmetic complex and 2) a field study on a night bus driver. All the tasks selected represent works with a dominant mental workload. The laboratory experiments showed the range of Critical Flicker Fusion Frequency (CFFF) at work of 14-40 HZ, with the average decline of CFFF values of 5.3 Hz in arithmetic complex and 4.8 Hz in critical reading activities. The study on the night bus driver resulted in CFFF value range of 18-40 Hz with the average delta CFFF of 8.97 Hz. Both testings suggest that flicker test with CFFF indicators can be used to measure mental fatigue. In addition, the proposed framework used in this design development can be used as a reference in designing various products by taking human factor aspects as the focus such as user needs and user limitations.